Opening the black pot: A service design-driven approach to understanding the use of cleaner cookstoves in peri-urban Kenya. (December 2020) - Lambe, Fiona; Ran, Ylva; Kwamboka, Elvine; Holmlid, Stefan; Lycke, Karin; Ringström, Susanne; Annebäck, Jenny; Ghosh, Emily; O'Conner, Margaret; Bailis, Rob
Abstract: Decades of efforts to replace traditional cooking methods that rely on solid biomass fuels with cleaner-burning and more energy-efficient cookstoves have fallen short of expectations, typically because the new stoves are only used for a short time, or they fail to fully displace the traditional methods. This points to a need to better understand how cookstove users assign value to the new cooking technologies. Recent research has shown that service design methods can help cookstove developers and programme implementers to better understand users' values, preferences, and needs and improve the stoves and supporting services to achieve greater success. This study builds on that work by combining service design methods and quantitative monitoring of cookstove usage in a small-scale pilot project to introduce clean burning biomass pellet cookstoves in two peri-urban areas outside Nairobi, Kenya. It identifies three different user archetypes, based on their primary motivation for trying new stoves – saving money, convenience, and health and safety. It finds critical weaknesses in the pilot intervention from the perspective of each archetype, and it verifies the findings of the qualitative analysis by reviewing the corresponding stove use monitoring data.